Stall‐side screening potential of a smartphone electrocardiogram recorded over both sides of the thorax in horses - Ignacio Corradini; Alicia Fernández‐Ruiz; Marta Barba; Javier Engel‐Manchado (Journal of Veterinary Internal Medicine, 2020)
Abstract Background Comparisons between smartphone ECG (SpECG) recordings obtained from the right and left sides of the thorax have not been reported in animals. Objectives To evaluate the screening potential of a SpECG obtained from both sides of the thorax and to compare the degree of agreement between the SpECG and a reference ECG (rECG) for measurement of the duration of baseline electrical deflections recorded over both sides of the thorax. Animals Fifty horses admitted to the equine hospital, university‐owned horses, and horses from an endurance riding facility. Methods Prospective observational study. Simultaneous rECG and SpECG tracings were recorded on both sides of the thorax and evaluated by 2 experienced observers for interpretability, presence and classification of arrhythmias, and duration of deflections of the electrical baseline. Results Fifteen (15/50) horses had spontaneous arrhythmias. Excellent agreement was found between the 2 devices (κ = 0.91; P < .001; 95% confidence interval [CI] 0.79‐1.03) for the detection of arrhythmias. Significantly more P waves were of diagnostic quality from the right side (20 versus 5, P = .001) and significantly more QRS and QT intervals were of diagnostic quality from the left side (66 versus 38 and 62 versus 34, respectively, P < .001). Substantial agreement for the duration of deflections between devices only was observed for the QRS interval (SpECG left). Conclusions and Clinical Importance It is important to obtain SpECG tracings from both sides of the thorax in horses. The SpECG is a useful stall‐sidearrhythmia‐screening tool for some common arrhythmias in horses.